Penatalaksanaan Sindrom Terowongan Karpal: Tinjauan Literatur - Sihaloho, Yohanna Christiani; Ismunandar, Helmi; Maulana, Muhammad (Medula, 2024)
Carpal tunnel syndrome is a group of symptoms caused by compression of the median nerve, resulting in increased carpal tunnel pressure on the wrist. Dominant paresthesia at night, pain that is worse at night, and weakness in the hands (for example, holding objects, making fists, and impaired fine motor skills in the hands) are symptoms that can occur in CTS sufferers. The incidence of CTS is estimated at 2.7-5.8% in the world, 7-16% in the UK, and 2.6 million adults (1.55%) experience CTS in the United States. The incidence of CTS is not yet known with certainty in Indonesia, but research in Denpasar reported that there was an incidence of CTS in workers of 79.2% (Paramita et al., 2021). CTS risk factors are divided into internal and external factors. Internal factors, including age, gender, nutritional status, pregnancy, menopause, other medical conditions (fracture or dislocation, diabetes mellitus, and rheumatoid arthritis). External factors, including repetitive wrist and hand movements, stiff and inappropriate work postures, long work duration. Physical and supporting examinations need to be carried out to help diagnose CTS. Examinations that can be carried out include provocation examinations, electrodiagnostic examinations and ultrasound examinations. Patients who have been diagnosed with CTS can be treated immediately to prevent further severity, including conservative therapy, pharmacological therapy, surgical therapy, or occupational therapy.